Second intention healing with guide sutures in mohs surgery: a reconstructive option. - Peña-Muñoz, Erika Andrea (2021)
Objective: To determine the aesthetic outcome of healing by second intention with guide sutures in Mohs surgery according to the concave, flat and convex anatomical areas of the face. Materials and methods: An observational descriptive study of a series of cases was carried out with 30 patients over 18 years of age, selected from the Oncoderma Clinic in Cali, post-operative for non-melanoma skin cancer through Mohs surgery, who were left in the process of healing by second intention with guide sutures, and after one year they underwent a control with a photographic record of the actress to which a SCAR evaluation scale was applied to measure the final aesthetic outcome. Results: The SCAR scale had an average score of 5.40 (SD 2.91). For the NEET anatomical area the average score was 4.15 (SD 2.2), followed by NOCH with 7.00 (SD 2.94) and the highest average score was for the FAIR area with 8.50 (SD 2, 07). In these scores there were significant differences between the groups (p = 0.001). Of the 20 scars evaluated in the NEET area, the rating was unacceptable only for 2 (10%) scars that scored 9 each. In contrast, the final score for most of the scars evaluated in the FAIR and NOCH areas was unacceptable; In the analysis of the FAIR area, it was found that the general impression was unacceptable for 5 (83.33%) scars of the 6 that make up this area in total, with a maximum score of 11 for 1 scar. The anatomical area NOCH, made up of 4 scars, had an unacceptable general impression for 3 (75%), of them, with a maximum score of 10 for 1 scar. Conclusions: The aesthetic outcome of second intention healing with guide sutures in Mohs surgery in concave anatomical areas was acceptable, but the results in flat areas of the face were unacceptable, as well as in convex areas.